SEPSIS NEONATORUM DAN PNEUMONIA PADA BAYI ATERM - Salendu, Praevilia M (UNIVERSITAS SAM RATULANGI, 2012)
Abstract: Sepsis neonatorum is the most frequent cause of admission to a hospital and of death in developing and developed countries. Microorganisms such as Gram positive and negative bacteria, viruses, parasites, and fungi can be the etiological factors. We reported a case of a female neonatus, aterm, and born with caesarean section due to fetal distress. After birth, the neonatus did not spontaneously cry and suffered from asphyxia. The risk factor of this sepsis neonatorum were the early rupture of the amnion membrane associated with an unpleasant odor. Besides that, the mother suffered from a urinary tract infection and fluor albus during pregnancy. Blood examinations showed moderate leucocytosis, slight thrombocytopenia, and a positive C-reactive protein. Chest X-ray showed infiltration in both lungs, indicating pneumonia. The blood culture confirmed Staphylococcus aureus (sensitive to meropenem). Conclusion: Based on all the tests performed, the diagnosis was an aterm neonatus with sepsis neonatorum and pneumonia. Keywords: sepsis, neonatus, pneumonia. Â Â Abstrak: Sepsis neonatorum merupakan penyebab tersering dari perawatan di rumah sakit dan kematian neonatus baik di negara berkembang maupun negara maju. Mikroba seperti bakteri Gram positif dan negatif, virus, parasit, serta jamur dapat menjadi faktor etiologi. Kami melaporkan kasus seorang bayi perempuan, aterm, yang lahir dengan seksio sesaria oleh karena gawat janin. Setelah lahir, bayi tidak langsung menangis, dan memperlihatkan gejala asfiksia. Faktor risiko sepsis neonatorum ialah ketuban pecah dini dan air ketuban berbau. Selain itu, ibu pasien menderita infeksi saluran kemih dan fluor albus pada saat hamil. Pemeriksaan darah menunjukkan leukositosis sedang, trombositopenia ringan, dan C-reaktif protein positif. Foto toraks memperlihatkan adanya infiltrat pada kedua lapangan paru yang mengindikasikan suatu pneumonia. Kultur darah mengonfirmasikan stafilokokus aureus yang sensitif terhadap meropenem. Simpulan: Berdasarkan hasil pemeriksaan ditegakkan diagnosis bayi aterm dengan sepsis neonatorum dan pneumonia. Kata kunci: sepsis, neonatus, pneumonia.